Integration of full divertor detachment with improved core confinement for tokamak fusion plasmas - L. Wang (Nature Portfolio, 2021)
Plasma fusion devices like tokamaks are important for energy generation but there are many challenges for their steady state operation. Here, the authors show that full divertor detachment is compatible with high-confinement high-poloidal-beta core plasmas and this prevents the damage to the divertor target plates and the first wall.